Improving the Thermal Performance of Liquid Metal Thermal Interface Materials: The Role of Intermetallic Compounds at the Gallium/Copper Interface - Xudong Zhang; Yuxia Dong; Yanzheng Du; Lei Yang; Weigang Ma; Bingyang Cao (Advanced Materials Interfaces)
Abstract Room‐temperature liquid metal has been widely used in electronic packaging due to its high thermal conductivity, but its thermal performance is strongly impeded by the dominated thermal boundary resistance between liquid metal and solid material. Here, first an order‐of‐magnitude reduction of thermal boundary resistance (from 1.11 × 10−7 (m2·K)/W to 6.94 × 10−9 (m2·K)/W) is reported by self‐synthesizing the intermetallic compound at the liquid gallium/solid copper interface. This significant thermal transport improvement is attributed to the conversion of heat carriers from phonons to electrons, and bonding force from van der Waals force to metallic bond, which is thoroughly analyzed by the microscopic phonon and electron diffuse mismatch models, complemented by molecular dynamic simulations. Chip application demonstrates that brushing liquid metal assisted by the intermetallic compound can surprisingly obtain the equivalent interfacial temperature difference (10.2 °C) to that of InSn solder welding (8.3 °C), which is much smaller than that of the conventional oxidation method (30.1 °C). This study provides a comprehensive understanding of electron/phonon transport at Ga/Cu interfaces and facilitates the giant thermal transport enhancement of liquid metal thermal interface material.